Canva Based Interactive Learning Media to Improve the Ability to Find the Main Idea of Grade IV Elementary School Students - Azizah, Nindia Nur; Ratnaningrum, Ika (International Journal of Elementary Education, 2025)
The limitations of teachers in utilizing and using less varied learning media result in students being less enthusiastic and not optimal in understanding the material and finding the main idea of grade IV. Teachers must create enjoyable learning to motivate students to improve their learning abilities. This study aims to develop interactive learning media based on Canva on the material to find the main idea of grade IV Elementary School. The type of research used is Research and Development (RnD) with the ADDIE development model. The subjects of this study consisted of expert validators of material and media, grade IV teachers, and grade IV students, totaling 25 people. In this study, the test techniques used were pretest and posttest, followed by non-test techniques using questionnaires, observations, interviews, and documentation. The data analysis technique used the Normality Test and T-Test, as well as the N-Gain Test, which was processed using SPSS Ver. 30. The results of the N-Gain Test from small groups and large groups obtained a value of 0.85 and a value of 0.86, which are included in the high category. It can be concluded that the development of interactive learning media based on Canva has proven to be effective and feasible to be used to improve students' ability to find main ideas, facilitate the learning process, and increase students' learning motivation in Indonesian language subjects. The results of this study imply that the use of interactive visual technology such as Canva in learning media can be an innovative strategy in creating active, enjoyable learning that has a positive impact on student learning outcomes.